2017
DOI: 10.1038/s41598-017-13383-3
|View full text |Cite
|
Sign up to set email alerts
|

White noise enhances new-word learning in healthy adults

Abstract: Research suggests that listening to white noise may improve some aspects of cognitive performance in individuals with lower attention. This study investigated the impact of white noise on new word learning in healthy young adults, and whether this effect was mediated by executive attention skills. Eighty participants completed a single training session to learn the names of twenty novel objects. The session comprised 5 learning phases, each followed by a recall test. A final recognition test was also administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 36 publications
(58 reference statements)
2
23
1
1
Order By: Relevance
“…Furthermore, this influence of white noise on cognitive performance has been attributed to dopamine release modulation 88 , 89 . However, in the learning and memory domain, this positive effect has been mainly observed in children with attention-deficit/hyperactivity disorder (ADHD) 90 , 91 , while it has been reported from mild to null when tested on healthy people 88 , 92 94 . Therefore, although results in relation to white noise must be interpreted with caution, the fact that no significant differences in memory performance have been observed between white noise and low-pleasure conditions discards the hypothesis that white noise could have driven a positive effect in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this influence of white noise on cognitive performance has been attributed to dopamine release modulation 88 , 89 . However, in the learning and memory domain, this positive effect has been mainly observed in children with attention-deficit/hyperactivity disorder (ADHD) 90 , 91 , while it has been reported from mild to null when tested on healthy people 88 , 92 94 . Therefore, although results in relation to white noise must be interpreted with caution, the fact that no significant differences in memory performance have been observed between white noise and low-pleasure conditions discards the hypothesis that white noise could have driven a positive effect in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In contradiction to the traditional belief that noise interferes with working memory performance (Schlittmeier et al 2015), recent findings see noise as a beneficial 'tool' that can be used effectively to enhance working memory performance (Abdul Manan et al 2012;Angwin et al 2017;Baijot et al 2016;Pickens et al 2019;Söderlund et al 2010;. However, the underlying neural mechanism of how noise improves AWM performance has not yet been well-established and demands further investigation.…”
Section: Discussionmentioning
confidence: 91%
“…Most recently, studies of stochastic facilitation have begun crossing disciplinary boundaries into human cognitive functions. Of particular interest are findings that white noise has the capacity to facilitate cognitive performance (Angwin et al 2017;Baijot et al 2016;Söderlund et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, various studies reported the results from the actions of white noise in the performance of activities (Liu et al, 2007;Söderlund et al, 2010). Also, these actions in learning have been reported (Angwin et al, 2017;Rausch et al, 2014;Vanessa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%